Increasing Students’ Pronunciation Mastery Through Spelling Words Strategy - Rista Respita; Suharti Siradjuddin; Sukmawati (CV. Eureka Murakabi Abadi, 2022)
This study aimed to improve students’ mastery of pronunciation through words spelling strategies in the fourth grade of SD Inpres Mappu in Mamuju. This research was a classroom action research (CAR) conducted in two cycles, namely, cycle one and cycle 2. Each cycle was carried out four times. There are four steps in this research; planning, action, observation, and reflection. The data in this study used quantitative (test) as the primary data and qualitative (field notes, recording, and documentation) as supporting data. The subjects in this study were 15 students in grade IV SD Inpres Mappu in Mamuju. The results showed that the use of the Words Spelling Strategy succeeded in improving the pronunciation master of the fourth-grade students of SD Inpres Mappu. It can be seen from the increased percentage of student learning outcomes from cycle I to cycle II, with an average value of 83.6. Therefore, it can be conducted that using the Words Spelling Strategy can improve student learning outcomes in mastering pronunciation.